Evaluation of lymphangiogenesis in acellular dermal matrix - Mario Cherubino; Igor Pellegatta; Federico Tamborini; Michele Cerati; Fausto Sessa; Luigi Valdatta (Indian Journal of Plastic Surgery)
Introduction: Much attention has been directed towards understanding the phenomena of angiogenesis and lymphangiogenesis in wound healing. Thanks to the manifold dermal substitute available nowadays, wound treatment has improved greatly. Many studies have been published about angiogenesis and cell invasion in INTEGRA®. On the other hand, the development of the lymphatic network in acellular dermal matrix (ADM) is a more obscure matter. In this article, we aim to characterize the different phases of host cell invasion in ADM. Special attention was given to lymphangiogenic aspects. Materials and Methods: Among 57 rats selected to analyse the role of ADM in lymphangiogenesis, we created four groups. We performed an excision procedure on both thighs of these rats: On the left one we did not perform any action except repairing the borders of the wound; while on the right one we used INTEGRA® implant. The excision biopsy was performed at four different times: First group after 7 days, second after 14 days, third after 21 days and fourth after 28 days. For our microscopic evaluation, we used the classical staining technique of haematoxylin and eosin and a semi-quantitative method in order to evaluate cellularity counts. To assess angiogenesis and lymphangiogenesis development we employed PROX-1 Ab and CD31/PECAM for immunohistochemical analysis. Results: We found remarkable wound contraction in defects that healed by secondary intention while minor wound contraction was observed in defects treated with ADM. At day 7, optical microscopy revealed a more plentiful cellularity in the granulation tissue compared with the dermal regeneration matrix. The immunohistochemical process highlighted vascular and lymphatic cells in both groups. After 14 days a high grade of fibrosis was noticeable in the non-treated group. At day 21, both lymphatic and vascular endothelial cells were better developed in the group with a dermal matrix application. At day 28, lymphatic endothelial cells had organized themselves, engineering the pseudocylindrical structure better disposed in the ADM group than in the control group, and the lymphatic cells were detectable inside the vessels’ lumen in this group. Conclusion: This study has made it possible to demonstrate the absolute importance of an ADM in proper wound healing and has shown better definition of both the qualitative and quantitative aspects of lymphangiogenesis compared to the second intention healing. A major grade of organization of the extracellular matrix and a minor grade of fibrosclerosis in ADM allowed a well-structured morphologic and functional development of the endothelial and lymphatic vascular structures. This study hopes to represent a clinical basis for a wider use of ADM in lesions where lymphatic complications are common.